Perancangan Sistem Informasi Laporan Penjualan Miss Cimory Berbasis Web Dengan Personal Extreme Programming - Indah Rizki Sahara Harahap; Hardiansyah (CV. Shofanah Media Berkah, 2023)
Miss Cimory plays a role in persuading the public so that people are interested in buying a product. This effort is carried out by various ways of communicating such as persuading, offering benefits or price discounts that can be attractive to buy a product being sold. The purpose of this study is to produce a sales report information system that can provide convenience in managing Cimory's sales management, especially managing financial data, recording and reporting sales transactions, and so that it can provide comfort to consumers. This research method was carried out using observation, interviews and library research, while the system development method used was the Extreme Programming (XP) method, which is one of the software development methods included in Agile Software Development. XP uses an object-oriented approach. The results of this sale also have an output, namely a sales report that was successfully initiated by Miss Cimori. Because this is what makes the writer want to do research on